Chemical approaches for the enhancement of porphyrin skeleton-based photodynamic therapy. (1st January 2020) - Lin, Yuyan; Zhou, Tao; Bai, Renren; Xie, Yuanyuan
Abstract: With the development of photodynamic therapy (PDT), remarkable studies have been conducted to generate photosensitisers (PSs), especially porphyrin PSs. A variety of chemical modifications of the porphyrin skeleton have been introduced to improve cellular delivery, stability, and selectivity for cancerous tissues. This review aims to highlight the developments in porphyrin-based structural modifications, with a specific emphasis on the role of PDT in anticancer treatment and the design of PSs to achieve a synergistic effect on multiple targets.